2019
DOI: 10.4049/jimmunol.1800363
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer’s Disease–Associated Protein BACE1 Modulates T Cell Activation and Th17 Function

Abstract: b-site amyloid precursor protein-cleaving enzyme 1 (BACE1) is best known for its role in Alzheimer's disease amyloid plaque formation but also contributes to neurodegenerative processes triggered by CNS injury. In this article, we report that BACE1 is expressed in murine CD4 + T cells and regulates signaling through the TCR. BACE1-deficient T cells have reduced IL-17A expression under Th17 conditions and reduced CD73 expression in Th17 and inducible T regulatory cells. However, induction of the Th17 and T regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 69 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…Surprisingly, recent studies identified that CD4+ T cells highly expressed BACE1, and BACE1 mediated T-cell activation in the EAE and AD mouse model (Dai et al, 2021;Hernandez-Mir et al, 2019).…”
Section: T-cell Function Is Associated With β-Secretasementioning
confidence: 99%
“…Surprisingly, recent studies identified that CD4+ T cells highly expressed BACE1, and BACE1 mediated T-cell activation in the EAE and AD mouse model (Dai et al, 2021;Hernandez-Mir et al, 2019).…”
Section: T-cell Function Is Associated With β-Secretasementioning
confidence: 99%
“…BACE1 has been shown to be important in Th17 differentiation 158 . BACE1 expression is upregulated in macrophage foam cell regions of atherosclerotic plaques 141 .…”
Section: Bace1 In Immune Functionmentioning
confidence: 99%
“…BACE1 is a transmembrane asparty1 protease that plays a role in forming plaques in AD (Vassar, 2004 ). BACE1-deficient T cells have reduced IL-17A expression under Th17 conditions in AD mouse models (Hernandez-Mir et al, 2019 ). However, the effect of IL-17A on the pathogenesis of AD is controversial.…”
Section: Role Of Il-17a In Neurodegenerative Diseasesmentioning
confidence: 99%